2,2'-Bis(meth-oxy-meth-oxy)-3-methyl-1,1'-binaphth-yl - Carrilho, Rui M. B. (2011)
The title compound, C(25)H(24)O(4), a meth-oxy-methyl (MOM) bis-protected BINOL derivative containing a methyl substituent in position 3, is a key inter-mediate for the synthesis of a great variety of chiral auxiliaries. The planes of the naphthyl aromatic rings are at an angle of 70.74 (3)°. There are no conventional hydrogen bonds binding the mol-ecules.